(untitled) (Trabalho & Educação, 2016)
This thesis analyzes the expansion policies of Vocational Education programs in Brazil and the role that Distance Education has in this context. This analysis will be achieved by the examination of a course offered through the E-Tec Network (Rede e-Tec) in a federal public institution. Specifically, this course’s guidelines and formational practices will be examined. The research present in this thesis was developed around three parameters: the trajectory of the Technical and Technological Vocational Education programs in Brazil beginning in 1990 and their expansion policies that were initiated in 2007; Distance Education and its incorporation in the scope of Public Policies for Vocational and Technological Education; and the implementation of the E-Tec Network (Rede e-Tec) in a federal public institution. The quantitative nature of this empirical research was conducted in an institution which adopted the E-Tec Brazil Program in 2008 and... __ Esta dissertação analisa as políticas de expansão da Educação Profissional no Brasil e o papel que a Educação a Distância ocupa nesse contexto, no escopo das diretrizes e práticas formativas de um curso ofertado por meio da Rede e-Tec em uma instituição pública federal. A pesquisa foi desenvolvida em torno de três eixos: a trajetória da Educação Profissional Técnica e Tecnológica no Brasil a partir de 1990 e sua política de expansão iniciada em 2007; a Educação a Distância e sua incorporação no âmbito das Políticas Públicas de Educação Profissional e Tecnológica; e a implementação da Rede e-Tec em uma instituição pública federal. A pesquisa empírica de natureza qualitativa foi realizada em uma instituição tradicionalmente reconhecida pela oferta de cursos técnicos de nível médio no Brasil, e que adotou o Programa e-Tec Brasil a partir de 2008...